Linguistic forms and The Meaning of Viral Words on Instagram - Sihindun Arumi; Giyatmi Giyatmi; Mas Sulis Setiyono (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
It was such a descriptive qualitative research that aimed at identifying the linguistic forms of viral words on Instagram and describing their meanings and contexts. The data were English words, phrases or sentences being viral on instagram. The source of the data was the captions or videos on instagram. The data were collected through observation and documentation. Observation was carried out by observing the words on instagram using English language. They then were documented by applying print screen (capturing the picture using computer) or screen shoot (capturing the picture using cellphone). The result of the research showed the occurrence of 286 data consisting of 153 data in the forms of words and 133 data in the form of phrases. The word form covered 17 words of ghosting, 18 words for roasting, 21 words of insecure, 15 of damage, review as many as 33, toxic as many as 8, vibes as many as 11, auto as many as 11, throwback as many as 10, and abbreviation OOTD as many as 9. In addition, the form of phrases as many as 133 consisted of close friend as many as 13, welcome to Indonesia as many as 30, be like as many as 19, no debat as many as 10, then now as many as 35, good looking as many as 16, and stay safe as many as 10. The results presented the fact that then now took the first place as many as 35. It showed that the users of Instagram mostly like to memorize their past. In other hand, review took the second place as many as 33. It explored the trend of showing one self’s strength. The last rank was taken by welcome to Indonesia as many as 30. It pointed the situation in Indonesia that need to be arranged well, either in areas of social, political, economic, etc.